2022
DOI: 10.1093/jme/tjac034
|View full text |Cite
|
Sign up to set email alerts
|

Survey and Phylogenetic Analysis of Leucocytozoon (Apicomplexa: Haemosporida) Parasites in Mississippi Black Flies (Diptera: Simuliidae)

Abstract: For several years, there have been continuous reports of black flies in Mississippi with evidence of transmission of Leucocytozoon spp. This study was conducted to determine the presence and diversity of Leucocytozoon spp. in black flies captured throughout Mississippi. Thirty-three collections, consisting of 346 specimens, were made during the 2-yr period (2015–2016) at 10 locations around the state. In addition to these systematic biweekly collections, 46 specimens were taken in 10 collections at four additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…First, we found a Leucocytozoon parasite (GenBank acc. Number OL897562) infecting Bubo bubo that has been previously identified in pooled samples of the blackfly Simulium meridionale captured throughout Mississippi, USA [54]. Second, Streptopelia decaocto, an avian host that had not been reported as infected by haemosporidians in previous studies, was found infected by Leucocytozoon ATNO1, a parasite lineage that had been previously recorded exclusively infecting the little owl (Athene noctua) (MalAvi database Version 2.5.8, October 2023, [13]).…”
Section: Prevalence and Genetic Diversity Of Haemosporidian Parasitesmentioning
confidence: 94%
“…First, we found a Leucocytozoon parasite (GenBank acc. Number OL897562) infecting Bubo bubo that has been previously identified in pooled samples of the blackfly Simulium meridionale captured throughout Mississippi, USA [54]. Second, Streptopelia decaocto, an avian host that had not been reported as infected by haemosporidians in previous studies, was found infected by Leucocytozoon ATNO1, a parasite lineage that had been previously recorded exclusively infecting the little owl (Athene noctua) (MalAvi database Version 2.5.8, October 2023, [13]).…”
Section: Prevalence and Genetic Diversity Of Haemosporidian Parasitesmentioning
confidence: 94%